Evaluasi Pelaksanaan Pembelajaran Akidah Akhlak Siswa Kelas Iv Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis - Sohibah, Sohibah; Peranginangin, Henri; Rahim, Abdur (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The phenomena that occur in the Gantar and surrounding areas, many school-age children whose morals are not good, speak impolitely, do not respect elders, and when they go to and from school, they ride motorbikes recklessly. From this phenomenon, the author wants to examine more deeply related to title that has been written above. This study aims to determine the Evaluation of the Implementation of Akhlak Akidah Learning for Class IV Students of Madrasah Ibtidaiyah Sukajati Haurgeulis This research examines the Evaluation of Learning Akhlak Akidah for Class IV Madrasah Ibtidaiyah Sukajati Haurgeulis. This research method uses a qualitative descriptive approach using a qualitative naturalistic approach. the object of this research is the fourth grade Madrasah Ibtidaiyah Madrasah Ibtidaiyah teacher, Akhlak Aqidah, Sukajati Haurgeulis. The data source for this research uses primary data and secondary data. Research procedures or data collection techniques use observation, interviews and documentation. The results of the study revealed that the Evaluation of the Implementation of Aqidah Akhlak Learning for Class IV Students of Madrasah Ibtidaiyah Sukajati Haurgeulis was in accordance with the curriculum. with the principal's instructions.